The effect of ball milling hours in the synthesizing nano-crystalline forsterite via solid-state reaction - Lai K.L.S.; Tan C.Y.; Ramesh S.; Tolouei R.; Yap B.K.; Amiriyan M. (2023)
The effect of ball milling hours on the manufacture of nano-crystalline forsterite powder was investigated in terms of particle size and phase stability. A quasi-mechanical activation method followed by heat treatment was successfully employed to produce nano-crystalline forsterite powder. During the attempt, ball milling hours were manipulated to study its effects on the particle size. XRD analysis was then conducted on the heat treated powders to determine the critical particle size. Based on XRD traces, it was revealed that 7 hours of low-energy ball milling was sufficient to produce crystalline forsterite powders. Subsequent FWHM studies also affirmed the critical particle size (? 41 nm) required to successfully transform MgO and Mg 3Si4O10(OH)2 into pure forsterite powder. 2011 Springer-Verlag.